Penentuan Jurusan Kuliah Menggunakan Metode Forward Chaining Berbasis Web - Mohamad Akbar Wisnu Nadyanto; Muhammad Varriel Avenazh Nizar; Aaqila Dhiyaanisafa Goenawan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
Determining majors is one of the obligations for all students who still want to continue their education. Decisions taken often cause problems when differences in abilities and limitations in thinking result in not graduating on time. Also, we often see majors chosen only because they follow the advice of friends or family and because of the development of the need for human resources in the world of work. Determination of majors should be done by considering the capabilities possessed. Therefore, this application was created which aims to design an expert system that can provide an overview for prospective students about what majors are suitable or in accordance with their abilities. The method used in making this expert system is Forward Chaining, where the facts related to determining the direction are stated first, then draw an appropriate conclusion. By making this application, it is expected to provide convenience for prospective students both in terms of time and cost.